(untitled) (Medico Legal Update, 2019)
Objectives: This study aimed to analyze the present and future of the work scope for emergency medical technicians (EMTs) in the South Korean emergency medical services system (EMSS). This is qualitative research with secondary data analysis based on literature review. Method: This is qualitative research aimed at interpreting and understanding the meanings of social and cultural phenomena. It aimed to investigate the social phenomena?current situations?of the work scope for EMTs in EMSS and make suggestions for increasing the scope in a future-oriented way. Result: As for the work scope for EMTs in South Korea, EMTs-Level 1 are in charge of airway intubation, laryngeal mask intubation, securing of an intravenous route, and medication (glucose injection against hypoglycemic coma, sublingual nitroglycerin against chest pain, a fixed amount of fluid infusion against shock, and bronchodilator inhalation against asthma exacerbation) in addition to those tasks of EMTs-Level 2. US EMTs-Paramedic are in charge of a wider range of tasks, including cardioversion and medication permitted in emergency, in addition to those tasks of EMTs-Basic and EMTs-Intermediate. Conclusion: EMTs actually play insignificant roles in South Korean EMSS. While the number of new good-quality EMTs increases on an annual basis, the scope of their work has insignificantly been changed for the past 20 years. South Korea needs to reinforce systems and legislation that can give good-quality EMS appropriate for advanced EMSS.